Influence Health Education Regarding Knowledge in Efforts to Prevent Early Teenage Marriage at SMK Negeri X Gorontalo - Suleman, Ibrahim; Pandaleke, Agnes (PT Inovasi Pratama Internasional, 2025)
In the current era of globalization, many problems occur, especially problems among teenagers which result in an increase in early marriage. Several factors ranging from behavior, knowledge, education, religion, parental education level, family socio-economics, place of residence, culture, decision making, access to information and promiscuity are causes of early marriage. Therefore, the role of all parties is very important, especially regarding health education which aims to change behavior in forming a structured mindset so that this becomes an effort to prevent early marriage. This research is a type of quantitative research using pre-experimental research methods, with a one group pretest-posttest research design. The population consisted of all 1,582 class X and XI students, sampling using the probability sampling method with a total of 158 students as samples. The research instrument used a questionnaire. The research results showed that there was an influence of health education on knowledge in efforts to prevent early marriage among teenagers at SMK Negeri Researchers realize that this research still has many shortcomings so it still needs to be developed, especially examining the factors that cause early marriage.